2008
DOI: 10.1111/j.1600-051x.2007.01185.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal conditions in patients with coronary heart disease: a case–control study

Abstract: Severe periodontal disease expressed by several clinical and radiographic parameters was more prevalent among subjects with CHD than among controls. Analysis, the factor periodontal disease experience groups 4+5 gave an odds ratio of 5.74 (2.07-15.90) for having CHD after controlling for smoking and age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The present study found that patients with AMI had more periodontal problems (fewer teeth, deeper pockets, more plaque and higher BOP), which is in line with the results reported by Starkhammar Johansson et al . and Geerts et al . .…”
Section: Discussionmentioning
confidence: 91%
“…The present study found that patients with AMI had more periodontal problems (fewer teeth, deeper pockets, more plaque and higher BOP), which is in line with the results reported by Starkhammar Johansson et al . and Geerts et al . .…”
Section: Discussionmentioning
confidence: 91%
“…It is considered that oral infectious processes can be implied in the inflammatory process and have an influence on the precipitation of acute coronary events; additionally, both diseases have complicated pathogeneses and clinical manifestations due to immune-system triggered inflammation (14) . Concerning this, a research (15) has found an association between PD and Coronary Artery Disease.…”
Section: Discussionmentioning
confidence: 97%
“…Although no significant association was found between periodontal disease and diabetes in the current study, researchers (17,18) evidenced a bidirectional association between the two diseases, i.e., diabetes favors the appearance of the PDPeriodontal disease and this one, when it is not treated, worsens the metabolic control of the diabetes. Besides this, the PD has a higher prevalence and seriousness in diabetic people when compared to the non-diabetic individuals (15) .…”
Section: Discussionmentioning
confidence: 99%
“…Microorganisms that cause this condition, interleukins, cross-reacting antibodies, etc. are involved [15][16][17][18][19][20][21][22][23][24][25][26]; something similar happens with the physiopathogenesis of atheromatous disease [10]. It is necessary to demonstrate how these two diseases interact in order to study the clinical impact and the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the differences between the case group and the control group are not clear since they are not detailed in the results; the number of patients expressed in the aim section does not match that in the results, making it difficult to interpret the findings (31) . Something similar happened with two systematic reviews which included different designs such as cross-sectional and casecontrol studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Our project, besides including matching risk factors mentioned in previous articles, incorporated vascular disease history in first degree relatives, sedentary lifestyle, number of teeth and BMI.…”
Section: Discussionmentioning
confidence: 99%